Epidemiologic aspects of male infertility - Velu, Arunadevi; Prasad, Geetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility affects 10-15% of couples worldwide with rates steadily increasing in the Industrialized world, in part due to the deterioration of male reproductive health. Methods: This study was performed in an attempt to clarify the associated factors that might play a role in group of Indian infertile men. This study was a cross – sectional descriptive study conducted in Karpaga Vinayaga Institute of Medical Sciences. The information was obtained from the men who had attended the clinic from January 2016-January 2017. The factors that were studied in this research are the demographic characteristics, alcohol consumption, smoking, exposure to heavy metals, obesity, stress and history of surgery. Results: In 31.6% of couples, the cause of infertility was pure male factor and in 20.4% of them the problem was related to male and female factor both. The most important associated factors for male factor included history of varicocele operation (24%), alcohol consumption (18%) and cigarette smoking (16%). Conclusions: Male factors play a significant role in up to 50 percent of infertility cases, stressing the need for a logical, stepwise approach to the evaluation of the male partner.